A Simulation Approach for Waste Reduction in the Bread Supply Chain - Arvind Bhardwaj; Rachit Soni; Lakhwinder Pal Singh; Rahul S Mor (Logistics)
Background: Bread, a basic need for the survival of human beings, is highly perishable, has a short shelf-life, and loses its quality and potency after its date of expiry. This leads to a considerable amount of bread waste and loss in the economy. This study explores and analyses the most common causes of wastage in the bread supply chain and proposes key strategies for waste mitigation in bread-producing industries in the context of Indian bakeries. Methods: Based on a systematic literature review and pilot studies, Monte-Carlo simulation techniques were applied to conduct the analysis. Results: The results indicate that bread should be recalled from the market after three days rather than the usual six, and the strategy used by companies A and E (in this study) is recommended. Conclusions: These tactics ensure that any bread returned to the company is in great condition, giving us two to three days to transform the bread into some by-products. It will help managers, decision makers, and specialists create a successful waste-reduction strategy.